Learning Indonesian through the Novel Supernova: Exploration of Social and Cultural Themes - Abdillah, Khumaidi; Amamy, Dinar (Proceeding International Conference on Education, 2024)
This research aims to explore the use of the novel Supernova by Dee Lestari as a medium for learning Indonesian, with a focus on social and cultural themes. A descriptive qualitative approach is used to analyze the symbolism in the novel and its thematic relevance in the context of modern Indonesian life. Data was collected through surveys, interviews and literature studies of 100 students and 10 secondary school teachers in Lamongan. The research results show that the majority of students and teachers consider the novel Supernova to be interesting and relevant teaching material, especially in introducing modern issues such as globalization, social class differences and spirituality. Symbols in the novel, such as technology and the universe, are used to represent the challenges of contemporary life and the search for meaning in life. Although some students have difficulty understanding symbolism and abstract themes, with the right guidance, this novel has been proven to improve students' critical thinking skills and broaden their social and cultural horizons. In conclusion, the novel Supernova is effectively used as teaching material in Indonesian language learning to deepen students' understanding of social and cultural phenomena.